Penelope and the feminism. The reinterpretation of a myth - Iván Pérez Miranda (FahrenHouse, 2007)
We try to analyze the figure of Penelope in Greek mythology, and how she has become one of the mythological prominent figures more reinterpreted throughout the times, with enormous influence in the art and the present culture.  rom certain feminist positions it has been wanted to see in Penelope role many characteristics that they would give us a supposition about the existence of a matriarchy, which was previous to the arrival of the patriarchy order. Nevertheless, we considered that the analysis of the sources demonstrate that powerful women such as Penelope, Areté,Yocasta or Níobe, had not the power by themselves, neither they have the character to be considered into the matriarchy parameters. The myth can transform itself to adapt to the new times, and it can serve to redefine the feminine gender and our current culture, but it must lead us neither to misinterpreting in an anachronistic way the past, nor to judging the ancient myths from a set of moral current values Key words: Penelope, Feminism, Classic Tradition, Myth, Gender.